Les femmes, l’environnement et le développement durable - Braidotti, Rosi; Charkiewicz, Ewa; Häusler, Sabine; Wieringa, Saskia (Genre, mouvements populaires urbains et environnement, 2007)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; discours dominant; environnement; histoire et politique; inégalités; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; systèmes d'oppressions; thématiques; écoféminisme

The scientific revolution and the death of nature - Merchant, Carolyn (Isis, 2006)
The Death of Nature: Women, Ecology, and the Scientific Revolution, published in 1980, presented a view of the Scientific Revolution that challenged the hegemony of mechanistic science as a marker of progress. It argued that seventeenth-century science could be implicated in the ecological crisis, the domination of nature, and the devaluation of women in the production of scientific knowledge. This essay offers a twenty-five-year retrospective of the book’s contributions to ecofeminism, environmental history, and reassessments of the Scientific Revolution. It also responds to challenges to the argument that Francis Bacon’s rhetoric legitimated the control of nature. Although Bacon did not use terms such as “the torture of nature,” his followers, with some justification, interpreted his rhetoric in that light.
https://nature.berkeley.edu/departments/espm/env-hist/articles/84.pdf
Keywords: approches et analyses; capitalisme; discipline; environnement; projet charge mentale; santé; santé de la nature; sciences; sciences de l'environnement; sexisme; systèmes d'oppressions; thématiques; torture de la nature; violences; écoféminisme